2018
DOI: 10.1007/s40620-018-0511-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate microRNA biomarkers in diabetic nephropathy: a meta-analysis of profiling studies

Abstract: Five highly significant and consistently dysregulated miRNAs were identified, and future studies should focus on discovering their potential effect on DN and their clinical value as DN biomarkers and therapeutic mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 87 publications
2
49
0
Order By: Relevance
“…Diagnostic significance of circulating miRNAs in systemic lupus erythematosus miR-21 originated from chromosome 17q23.2 immediately to the vacuole membrane protein 1 gene and played an important role in regulating cell differentiation and proliferation [51][52]. Furthermore, miR-21 was considered as a promising biomarker of many diseases [53][54][55]. Also, previous studies suggested that miR-21 regulated aberrant responses of T cells of SLE [56][57], modulation of miR-21 expressions might restore the function of Treg cells and in turn reverse the clinical manifestations of SLE [19].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic significance of circulating miRNAs in systemic lupus erythematosus miR-21 originated from chromosome 17q23.2 immediately to the vacuole membrane protein 1 gene and played an important role in regulating cell differentiation and proliferation [51][52]. Furthermore, miR-21 was considered as a promising biomarker of many diseases [53][54][55]. Also, previous studies suggested that miR-21 regulated aberrant responses of T cells of SLE [56][57], modulation of miR-21 expressions might restore the function of Treg cells and in turn reverse the clinical manifestations of SLE [19].…”
Section: Discussionmentioning
confidence: 99%
“…The miR-223-3p expression appears to be affected by renal diseases as its expression was shown to be reduced in both acute and chronic kidney diseases 34,35 . miR-25-3p was also shown to be downregulated in diabetic nephropathy, suggesting an influence of renal disease on its expression 36 . Although there are no previous studies examining the relationship between miR-223-3p, miR-25-3p, and hepatic encephalopathy, the association observed here indicate that expression of these miRNAs may be affected by the severity of the liver disease.…”
Section: Variablesmentioning
confidence: 98%
“…Guo et al [18] expounded that upregulated miR-29c increased the expression of inflammatory cytokines and promoted the progress of DN in DN patients. A meta-analysis on the miRNA expression profile in DN revealed downreglulation of miR-34c in at least two studies [19]. Recent studies observed that miR-34c inhibited HG-induced cell death in podocytes [20] and suppressed inflammasome activity in astrocytes, microglia, and neurons [21].…”
Section: Introductionmentioning
confidence: 99%